Antistatic and flame-retardant polystyrene composite material and preparation method and application thereof

By using graphite nanosheets modified with sodium dodecylbenzenesulfonate in foamed polystyrene composites, the problems of material flammability and electrostatic accumulation are solved, and the anti-static and flame retardant properties are improved, and the process is simple and environmentally friendly.

CN118496401BActive Publication Date: 2025-04-15LIAONING LITIAN NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410694756.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-04-15
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

Existing foamed polystyrene composites have problems of flammability and electrostatic accumulation, which limits their wide application in the fields of thermal insulation and packaging.

Method used

Graphite nanosheets modified with sodium dodecylbenzenesulfonate were used as filler materials, and antistatic and flame-retardant polystyrene composite materials were prepared through doping polymerization and foaming processes.

Benefits of technology

The electrostatic dispersion and flame retardant properties of polystyrene composite materials have been improved, and the preparation process is simple, environmentally friendly and low-cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118496401B_ABST
    Figure CN118496401B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of foamed polystyrene composite materials, and in particular to an antistatic and flame-retardant polystyrene composite material and a preparation method and application thereof. The present invention provides an antistatic and flame-retardant polystyrene composite material, wherein the raw materials for preparation include graphite nanosheets modified by sodium dodecylbenzene sulfonate; the amount of the graphite nanosheets modified by sodium dodecylbenzene sulfonate in the antistatic and flame-retardant polystyrene composite material is 1 to 8 wt %. The graphite nanosheets modified by sodium dodecylbenzene sulfonate can make the preparation process of the antistatic and flame-retardant polystyrene composite material simple and green.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foamed polystyrene composite materials, and in particular to an antistatic and flame-retardant polystyrene composite material and a preparation method and application thereof. Background Art

[0002] Expandable polystyrene (EPS) has excellent properties such as low thermal conductivity, low water absorption, sound insulation, moisture resistance, shock resistance, strong impact resistance and simple molding process. Although EPS has been widely used in the fields of thermal insulation and packaging, its flammability has led to a large number of fire accidents. At the same time, the insulation of EPS makes it have the property of charge accumulation, which can cause electrical equipment failure and damage during the static discharge process. The research and development of EPS composite materials with good electrical conductivity and flame retardancy has important industrial application value.

[0003] At present, the use of carbon materials to fill expanded polystyrene is a research hotspot. Among them, polystyrene composites prepared using materials such as carbon nanotubes, graphene and acetylene black have the advantages of high mechanical strength and low thermal conductivity. In existing studies, the preparation process of the carbon nanotubes, graphene and acetylene black used is complicated and the materials are expensive, which restricts their commercial application in enhancing EPS composites. It is worth noting that there are no reports on the dispersibility, filling amount and effect of filling of two-dimensional graphene nanosheets in polystyrene on the conductivity and flame retardancy of expanded polystyrene. Therefore, based on the concept of green chemistry, it is of great research and development value to select a simple and low-cost nanocarbon material as a filling raw material to prepare expanded polystyrene composites with both electrostatic dispersion properties (or antistatic properties) and flame retardancy. Summary of the invention

[0004] The purpose of the present invention is to provide an antistatic and flame-retardant polystyrene composite material and a preparation method and application thereof. The graphite nanosheets modified by sodium dodecylbenzene sulfonate can make the preparation process of the antistatic and flame-retardant polystyrene composite material simple and green.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides an antistatic and flame-retardant polystyrene composite material, the preparation raw materials of which include graphite nanosheets modified by sodium dodecylbenzene sulfonate;

[0007] The content of the graphite nanosheets modified by sodium dodecylbenzene sulfonate in the antistatic and flame-retardant polystyrene composite material is 1 to 8 wt %.

[0008] Preferably, the preparation raw materials also include styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite.

[0009] Preferably, the preparation raw materials include 0.2 to 1.6 parts of graphite nanosheets modified with sodium dodecylbenzene sulfonate, 20 parts of styrene monomer, 80 parts of water, 0.5 to 4 parts of dibenzoyl peroxide, 0.3 to 0.9 parts of anhydrous sodium carbonate, 0.003 to 0.039 parts of sodium dodecylbenzene sulfonate, 0.1 to 0.5 parts of anhydrous sodium bisulfite and 0.14 to 1.29 parts of hydroxyapatite, calculated by weight.

[0010] Preferably, the method for preparing the graphite nanosheets modified with sodium dodecylbenzene sulfonate comprises the following steps:

[0011] The dispersion of graphite nanosheets is mixed with hydrogen peroxide and oxidized to obtain oxidized graphite nanosheets;

[0012] The oxidized graphite nanosheets, water and sodium dodecylbenzene sulfonate are mixed and modified to obtain graphite nanosheets modified with sodium dodecylbenzene sulfonate.

[0013] Preferably, the mass ratio of graphite nanosheets to sodium dodecylbenzene sulfonate in the dispersion of graphite nanosheets is 5:(0.05-0.25);

[0014] The modification temperature is 50-85° C. and the modification time is 2-8 hours.

[0015] The present invention also provides a method for preparing the antistatic and flame-retardant polystyrene composite material described in the above technical solution, comprising the following steps:

[0016] The graphite nanosheets modified by sodium dodecylbenzene sulfonate, styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite are mixed and doped and polymerized to obtain polystyrene beads doped with the modified graphite nanosheets;

[0017] The modified graphite nanosheet-doped polystyrene beads are soaked in water and then foamed by passing carbon dioxide to obtain the antistatic and flame-retardant polystyrene composite material.

[0018] Preferably, the mass ratio of the sodium dodecylbenzene sulfonate-modified graphite nanosheets, styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite is (0.2-1.6):20:80:(0.5-4):(0.3-0.9):(0.003-0.039):(0.1-0.5):(0.14-1.29).

[0019] Preferably, the process of the doping polymerization is: at a stirring rate of 180-225 rpm, after being placed in a 40-50° C. water bath for 1-2 hours, heating to 90-92° C. at a heating rate of 1° C. / min, increasing the stirring speed to 350-400 rpm, and keeping warm for 2.5-4 hours.

[0020] Preferably, the foaming process is: under a pressure of 4 to 4.5 MPa, the temperature is raised to 100 to 110° C. at a heating rate of 15° C. / 10 min, and the temperature is kept for 5 to 7 hours before the carbon dioxide is discharged.

[0021] The present invention also provides the use of the antistatic and flame-retardant polystyrene composite material described in the above technical solution or the antistatic and flame-retardant polystyrene composite material prepared by the preparation method described in the above technical solution in the fields of thermal insulation and packaging of chemical equipment, electrical instruments or buildings.

[0022] The invention provides an antistatic and flame-retardant polystyrene composite material, wherein the raw materials for preparation include graphite nanosheets modified by sodium dodecylbenzene sulfonate; the amount of the graphite nanosheets modified by sodium dodecylbenzene sulfonate in the antistatic and flame-retardant polystyrene composite material is 1-8wt%. The graphite nanosheets modified by sodium dodecylbenzene sulfonate are used as fillers in the invention, so that the graphite nanosheets modified by sodium dodecylbenzene sulfonate can be in-situ doped during the polymerization of styrene in the preparation process of polystyrene, so that the graphite nanosheets modified by sodium dodecylbenzene sulfonate are uniformly dispersed in polystyrene balls, and the polystyrene composite material has good electrostatic dispersion (or antistatic) and flame retardancy. At the same time, the invention adjusts the electrostatic dispersion or antistatic performance and flame retardancy of the antistatic and flame-retardant polystyrene composite material by controlling the amount of the graphite nanosheets modified by sodium dodecylbenzene sulfonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 HR-TEM image of the graphite nanosheet prepared in Example 1;

[0024] Figure 2 HR-TEM image of the graphite nanosheets prepared in Example 2;

[0025] Figure 3 This is a SEM image of the graphite nanosheets prepared in Example 3;

[0026] Figure 4 HR-TEM image of the graphite nanosheets prepared in Example 3;

[0027] Figure 5 XRD patterns of polystyrene beads doped with modified graphite nanosheets and polystyrene beads not doped with modified graphite nanosheets described in Examples 5, 6, 7, and 8;

[0028] Figure 6 This is a cross-sectional SEM image of a polystyrene ball doped with modified graphite nanosheets having a doping amount of 1 wt % prepared in Example 5;

[0029] Figure 7 This is a cross-sectional SEM image of a polystyrene ball doped with modified graphite nanosheets with a doping amount of 8 wt % prepared in Example 8;

[0030] Figure 8 This is a cross-sectional SEM image of polystyrene spheres doped with graphite nanosheets with a doping amount of 1 wt % prepared in a comparative example. DETAILED DESCRIPTION

[0031] The present invention provides an antistatic and flame-retardant polystyrene composite material, the preparation raw materials of which include graphite nanosheets modified by sodium dodecylbenzene sulfonate;

[0032] The content of the graphite nanosheets modified by sodium dodecylbenzene sulfonate in the antistatic and flame-retardant polystyrene composite material is 1 to 8 wt %.

[0033] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0034] In the present invention, the method for preparing the graphite nanosheets modified with sodium dodecylbenzene sulfonate preferably comprises the following steps:

[0035] The dispersion of graphite nanosheets is mixed with hydrogen peroxide and oxidized to obtain oxidized graphite nanosheets;

[0036] The oxidized graphite nanosheets, water and sodium dodecylbenzene sulfonate are mixed and modified to obtain graphite nanosheets modified with sodium dodecylbenzene sulfonate.

[0037] The invention mixes the dispersion liquid of graphite nanosheets and hydrogen peroxide, and performs oxidation to obtain oxidized graphite nanosheets.

[0038] In the present invention, the mass ratio of graphite nanosheets to water in the dispersion of graphite nanosheets is preferably 1:(20-100), more preferably 1:(40-70), and most preferably 1:60. The water is preferably deionized water.

[0039] In the present invention, the method for preparing the graphite nanosheets preferably comprises the following steps:

[0040] Natural graphite, concentrated sulfuric acid and calcium hypochlorite are mixed and reacted to obtain expandable graphite;

[0041] Expanding the expandable graphite at high temperature to obtain expanded graphite;

[0042] The expanded graphite and water are mixed and then sand-milled to obtain graphite nanosheets.

[0043] The invention prepares expandable graphite by mixing natural graphite, concentrated sulfuric acid and calcium hypochlorite and reacting them.

[0044] In the present invention, the mass concentration of the concentrated sulfuric acid is preferably 98%; the natural graphite is preferably natural flake graphite. In the present invention, the mass ratio of the natural graphite, concentrated sulfuric acid and calcium hypochlorite is preferably (2-5):10:(0.5-2), more preferably (2-3):10:(1-1.5), and most preferably 2:10:1. The present invention does not have any special restrictions on the mixing process, and the process well known to those skilled in the art can be used.

[0045] In the present invention, the reaction temperature is preferably 25° C., the reaction time is preferably 4 to 9 h, more preferably 5 to 7 h, and most preferably 6 h.

[0046] After the reaction is completed, the present invention also preferably includes the first suction filtration, the first water washing, neutralization, the second suction filtration, the second water washing, the removal of calcium ions, the third suction filtration and drying in sequence; the present invention has no special restrictions on the process of the first suction filtration, and the process well known to those skilled in the art can be used to ensure the purpose of deacidification; the present invention has no special restrictions on the process of the first water washing, and the process well known to those skilled in the art can be used. In the present invention, the neutralization is preferably carried out by sodium carbonate; the mass ratio of the natural graphite and sodium carbonate is preferably (5-7): 1, more preferably 5: 1. The present invention has no special restrictions on the process of the second suction filtration and the second water washing, and the process well known to those skilled in the art can be used. In the present invention, the process of removing the calcium ions is preferably achieved by adding concentrated acid salts; the mass concentration of the concentrated hydrochloric acid is preferably 36%; the mass ratio of the natural graphite and concentrated hydrochloric acid is preferably 5: (2-4), more preferably 5: 3. The present invention has no special restrictions on the process of the third suction filtration, and the process well known to those skilled in the art can be used. In the present invention, the temperature of the drying is preferably 100°C and the time is preferably 5h.

[0047] After the expandable graphite is obtained, the present invention expands the expandable graphite at high temperature to obtain expanded graphite.

[0048] In the present invention, the temperature of the high temperature expansion is preferably 830-900°C, more preferably 840-860°C, and most preferably 850°C; the time is preferably 30-90s, more preferably 50-70s, and most preferably 60s. In the present invention, the high temperature expansion is preferably carried out in a muffle furnace.

[0049] After the expanded graphite is obtained, the invention mixes the expanded graphite with water and performs sand milling to obtain graphite nanosheets.

[0050] In the present invention, the water is preferably deionized water; the ratio of the expanded graphite to water is preferably 1:40 to 100, more preferably 1:50 to 60, and most preferably 1:50. The present invention does not have any special limitation on the mixing process, and the process well known to those skilled in the art can be used.

[0051] In the present invention, the sand mill preferably uses zirconia beads with a diameter of 2 mm. In the present invention, the mass ratio of the expanded graphite to the zirconia beads is preferably 1:50-100, more preferably 1:100. In the present invention, the rotation speed of the sand mill is preferably 4000-10000 rpm, more preferably 5000-8000 rpm, and most preferably 6000 rpm; the sand milling time is preferably 3-10 hours, more preferably 6-10 hours, and most preferably 8-9 hours.

[0052] In the present invention, the mass concentration of the hydrogen peroxide is preferably 20wt% to 50wt%, more preferably 20wt% to 35wt%, and most preferably 25wt%.

[0053] In the present invention, the amount ratio of graphite nanosheets to hydrogen peroxide in the dispersion of graphite nanosheets is preferably 1 g:2-5 mL, more preferably 1 g:3-4 mL, and most preferably 1 g:3 mL.

[0054] In the present invention, the oxidation is preferably carried out under ultrasonic conditions, the ultrasonic temperature is preferably 20-35°C, more preferably 20-30°C, most preferably 25°C; the ultrasonic time is preferably 0.5-3h, more preferably 0.8-1.5h, most preferably 1h.

[0055] After the oxidation is completed, the present invention also preferably includes suction filtration and washing performed in sequence. The present invention has no special limitation on the suction filtration process, and the process well known to those skilled in the art can be used. In the present invention, the washing is preferably performed with deionized water.

[0056] After the washing is completed, the present invention preferably does not perform any post-treatment on the obtained filter cake, and the obtained filter cake is kept in a wet state and the subsequent modification process is performed.

[0057] After obtaining the oxidized graphite nanosheets, the present invention mixes the oxidized graphite nanosheets, water and sodium dodecylbenzene sulfonate to perform modification, thereby obtaining the graphite nanosheets modified by sodium dodecylbenzene sulfonate.

[0058] In the present invention, the water is preferably deionized water. In the present invention, the mass ratio of the graphite nanosheets to sodium dodecylbenzene sulfonate is preferably 5:(0.05-0.25), more preferably 5:(0.10-0.20), and most preferably 5:(0.13-0.16). In the present invention, the mass ratio of the water to sodium dodecylbenzene sulfonate is preferably 80:(0.05-0.25), more preferably 80:(0.10-0.20), and most preferably 80:(0.13-0.16). The present invention does not have any special restrictions on the mixing process, and the process well known to those skilled in the art can be used.

[0059] In the present invention, the modification temperature is preferably 50-85°C, more preferably 55-70°C, and most preferably 60°C; the modification time is preferably 2-8h, more preferably 5-7h, and most preferably 6h. In the present invention, the modification is preferably carried out in a water bath.

[0060] After the modification is completed, the present invention also preferably includes sequential filtration and water washing. The present invention has no special limitation on the filtration and water washing process, and the filtration and water washing process can be performed using a process well known to those skilled in the art.

[0061] In the present invention, the raw materials for preparing the antistatic and flame-retardant polystyrene composite material preferably further include styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite.

[0062] In the present invention, the amount of the graphite nanosheets modified with sodium dodecylbenzene sulfonate is preferably 0.2 to 1.6 parts by mass, more preferably 0.5 to 1.0 parts by mass, and most preferably 0.6 to 0.8 parts by mass.

[0063] Based on the mass fraction of the sodium dodecylbenzene sulfonate-modified graphite nanosheets, the raw materials for preparing the antistatic and flame-retardant polystyrene composite material of the present invention preferably include 20 parts of styrene monomer.

[0064] Based on the mass fraction of the sodium dodecylbenzenesulfonate-modified graphite nanosheets, the raw materials for preparing the antistatic and flame-retardant polystyrene composite material of the present invention preferably include 0.5 to 4 parts of dibenzoyl peroxide, more preferably 1 to 3 parts, and most preferably 1.5 to 2.5 parts.

[0065] Based on the mass fraction of the graphite nanosheet modified by sodium dodecylbenzene sulfonate, the raw material for preparing the antistatic and flame-retardant polystyrene composite material of the present invention preferably includes 0.3 to 0.9 parts of anhydrous sodium carbonate, preferably 0.4 to 0.8 parts, and more preferably 0.5 to 0.6 parts. In the present invention, the function of the anhydrous sodium carbonate is to neutralize the inhibitor in the styrene monomer and stabilize the pH value of the reaction solution to be weakly alkaline.

[0066] Based on the mass fraction of the graphite nanosheets modified by sodium dodecylbenzene sulfonate, the raw materials for preparing the antistatic and flame-retardant polystyrene composite material of the present invention preferably include 0.003 to 0.039 parts of sodium dodecylbenzene sulfonate, preferably 0.010 to 0.030 parts, and more preferably 0.015 to 0.025 parts. In the present invention, the role of the sodium dodecylbenzene sulfonate is to play a surfactant role in the polymerization process.

[0067] Based on the mass fraction of the graphite nanosheet modified by sodium dodecylbenzene sulfonate, the raw material for preparing the antistatic and flame-retardant polystyrene composite material of the present invention preferably includes 0.1 to 0.5 parts of anhydrous sodium bisulfite, preferably 0.2 to 0.4 parts, and more preferably 0.25 to 0.35 parts. In the present invention, the function of the anhydrous sodium bisulfite is to prevent the oxidation of the initiator.

[0068] Based on the mass fraction of the sodium dodecylbenzene sulfonate modified graphite nanosheets, the raw materials for preparing the antistatic and flame-retardant polystyrene composite material of the present invention preferably include 0.14 to 1.29 parts of hydroxyapatite, preferably 0.3 to 1.0 parts, and more preferably 0.5 to 0.8 parts. In the present invention, the role of the hydroxyapatite is to prevent the prepared polystyrene microspheres from merging and to play a dispersing role.

[0069] The present invention also provides a method for preparing the antistatic and flame-retardant polystyrene composite material described in the above technical solution, comprising the following steps:

[0070] The graphite nanosheets modified by sodium dodecylbenzene sulfonate, styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite are mixed and doped and polymerized to obtain polystyrene beads doped with the modified graphite nanosheets;

[0071] The modified graphite nanosheet-doped polystyrene beads are soaked in water and then foamed by passing carbon dioxide to obtain the antistatic and flame-retardant polystyrene composite material.

[0072] Graphite nanosheets modified with sodium dodecylbenzene sulfonate, styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite are mixed and doped and polymerized to obtain polystyrene beads doped with the modified graphite nanosheets.

[0073] In the present invention, the process of doping polymerization is preferably carried out at a stirring rate of 180 to 225 rpm, in a 40 to 50° C. water bath for 1 to 2 hours, then heated to 90 to 92° C. at a heating rate of 1° C. / min, and then the stirring speed is increased to 350 to 400 rpm, and then kept warm for 2.5 to 4 hours; more preferably, at a stirring rate of 225 rpm, in a 50° C. water bath for 1 hour, then heated to 90° C. at a heating rate of 1° C. / min, and then the stirring speed is increased to 375 rpm, and then kept warm for 2.5 hours.

[0074] After the doping polymerization is completed, the present invention also preferably includes the step of cooling the obtained polystyrene beads to room temperature after they are all hardened and sank, washing them three times with deionized water, and then drying them. The drying temperature is preferably 60° C. and the drying time is preferably 12 hours.

[0075] After obtaining the modified graphite nanosheet-doped polystyrene beads, the present invention soaks the modified graphite nanosheet-doped polystyrene beads in water and then passes carbon dioxide through the water for foaming to obtain the antistatic and flame-retardant polystyrene composite material.

[0076] In the present invention, the soaking time is preferably 6 to 15 hours, more preferably 9 to 12 hours, and most preferably 10 hours.

[0077] In the present invention, the temperature of the carbon dioxide is preferably room temperature. The pressure after the carbon dioxide is introduced is preferably 3 to 5 MPa, more preferably 4 to 5 MPa, and most preferably 4.5 MPa.

[0078] In the present invention, the foaming process is preferably carried out under a pressure of 4 to 4.5 MPa, at a heating rate of 15°C / 10min to 100 to 110°C, and after keeping the temperature for 5 to 7 hours, the carbon dioxide is discharged; more preferably, under a pressure of 4.5 MPa, at a heating rate of 15°C / 10min to 110°C, and after keeping the temperature for 6 hours, the carbon dioxide is discharged. In the present invention, the process of discharging carbon dioxide is preferably to discharge carbon dioxide within 20 seconds.

[0079] After the foaming is completed, the present invention preferably includes cooling; the present invention has no special limitation on the cooling process, and the cooling process may be carried out using a process well known to those skilled in the art.

[0080] The present invention also provides the use of the antistatic and flame-retardant polystyrene composite material described in the above technical solution or the antistatic and flame-retardant polystyrene composite material prepared by the preparation method described in the above technical solution in the field of thermal insulation and packaging of chemical equipment, electrical instruments or buildings. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.

[0081] The antistatic and flame-retardant polystyrene composite material provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0082] Example 1

[0083] Preparation of graphite nanosheets: 10g of natural flake graphite, 75g of concentrated sulfuric acid and 5g of calcium hypochlorite were mixed, reacted at 25°C for 6h, and then filtered for deacidification and washed with water; 2g of sodium carbonate was added, filtered and washed with water, 6g of concentrated hydrochloric acid was added to remove possible residual calcium ions, and filtered until the filtrate was neutral; the filter cake obtained by filtration was dried at 100°C for 5h to obtain an expandable graphite sample;

[0084] After the expandable graphite sample was expanded at 850° C. for 60 seconds in a muffle furnace, the obtained expanded graphite was dispersed in 500 mL of deionized water and sand-milled at 6000 rpm for 3 hours using 1000 g of zirconia beads (with a diameter of 2 mm) to obtain graphite nanosheets.

[0085] Preparation of modified graphite nanosheets: 5 g of the above graphite nanosheets and 300 mL of deionized water were placed in a beaker, 15 mL of hydrogen peroxide with a mass concentration of 25% was added, the beaker was placed in an ultrasonicator for ultrasonication (25°C, 1 h), and then filtered and washed with deionized water in sequence to obtain a wet filter cake (graphite nanosheets oxidized with hydrogen peroxide);

[0086] The wet filter cake was placed in a beaker, and 80 mL of deionized water and 0.05 g of sodium dodecylbenzene sulfonate (SDBS) were added at the same time. The mixture was modified in a water bath at 60° C. for 6 h, and then filtered and washed with water to obtain SDBS-modified graphite nanosheets (the filter cake was kept wet and the solid content was tested by sampling. The wet filter cake was placed in a sample bag and sealed at low temperature for storage);

[0087] Polystyrene beads doped with modified graphite nanosheets: 0.2 g (dry basis) of the SDBS-modified highly graphite nanosheets were added to a three-necked flask, and 20 g of styrene monomer, 80 mL of deionized water, 0.5 g of dibenzoyl peroxide (BPO), 0.3 g of anhydrous sodium carbonate, 0.003 g of sodium dodecylbenzene sulfonate, 0.1 g of anhydrous sodium bisulfite and 0.14 g of hydroxyapatite were added. The three-necked flask was placed in a constant temperature water bath, the initial stirring speed was adjusted to 180 rpm, the water bath temperature was adjusted to 40° C. for 1 h, and then the temperature was raised to 90° C. at a heating rate of 1° C. / min, and the stirring speed was increased to 350 rpm and maintained for 2.5 h until all the polystyrene beads were hardened and sank, and then the stirring was stopped, and the mixture was naturally cooled to room temperature, and washed repeatedly with deionized water for three times, and dried at 60° C. for 12 h to obtain polystyrene beads (particle size of 0.8-1.2 mm) doped with modified graphite nanosheets with a doping amount of 1 wt%;

[0088] Polystyrene foam doped with modified graphite nanosheets: After soaking 10 g of the polystyrene balls doped with modified graphite nanosheets in deionized water for 10 hours, the soaked doped modified graphite nanosheets are placed in a reactor, 100 mL of deionized water is added to the reactor and the reactor is closed. CO2 gas is introduced into the reactor at room temperature. When the pressure in the reactor reaches 4.5 MPa, ventilation is stopped and the temperature is slowly increased (heating rate is 15°C / 10min) to 110°C and maintained for 7 hours. The CO2 gas in the reactor is discharged within 20 seconds, the reactor is opened, and the temperature is lowered to room temperature to obtain a polystyrene foam doped with modified graphite nanosheets with a doping amount of 1wt%.

[0089] Figure 1 is the HR-TEM image of the graphite nanosheet, Figure 1 It can be seen that the thickness of the graphite nanosheets prepared by the present invention is 8.3 nm.

[0090] Example 2

[0091] Refer to Example 1, except that (1) the sand milling time is adjusted to 6 h during the preparation of graphite nanosheets; (2) Polystyrene beads doped with modified graphite nanosheets: 0.2 g (dry basis) of the SDBS-modified graphite nanosheets are added to a three-necked flask, and 20 g of styrene monomer, 80 mL of deionized water, 0.5 g of dibenzoyl peroxide (BPO), 0.3 g of anhydrous sodium carbonate, 0.003 g of sodium dodecylbenzene sulfonate, 0.1 g of anhydrous sodium bisulfite and 0.14 g of hydroxyapatite are added at the same time. The three-necked flask was placed in a thermostatic water bath, the initial stirring speed was adjusted to 225 rpm, the water bath temperature was adjusted to 50° C. for 2 h, and then the temperature was raised to 92° C. at a heating rate of 1° C. / min, and the stirring speed was increased to 400 rpm and maintained for 4 h until all the polystyrene beads were hardened and sank, and then the stirring was stopped, and the mixture was naturally cooled to room temperature, and washed repeatedly with deionized water for three times, and dried at 60° C. for 12 h to obtain polystyrene beads (particle size of 0.8-1.2 mm) doped with modified graphite nanosheets with a doping amount of 1 wt%;

[0092] Figure 2 is the HR-TEM image of the graphite nanosheet, Figure 2 It can be seen that the thickness of the graphite nanosheets prepared by the present invention is 5.8 nm.

[0093] Example 3

[0094] Refer to Example 1, except that (1) in the process of preparing graphite nanosheets, the sand grinding time is adjusted to 9 hours; (2) polystyrene foam doped with modified graphite nanosheets: 10g of the polystyrene balls doped with modified graphite nanosheets are soaked in deionized water for 10 hours, and then the soaked doped modified graphite nanosheets are put into a reactor, 100mL of deionized water is added to the reactor and then the reactor is closed. CO2 gas is introduced into the reactor at room temperature. When the pressure in the reactor reaches 4MPa, ventilation is stopped and the temperature is slowly increased (the heating rate is 15℃ / 10min) to 100℃ and maintained for 5 hours. Then, the CO2 gas in the reactor is discharged within 20s, the reactor is opened, and the temperature is cooled to room temperature to obtain polystyrene foam doped with modified graphite nanosheets with a doping amount of 1wt%.

[0095] Figure 3 is the SEM image of the graphite nanosheet, Figure 3 It can be seen that the average particle size of the graphite nanosheets prepared by the present invention is 15.3 μm;

[0096] Figure 4 is the HR-TEM image of the graphite nanosheet, Figure 4 It can be seen that the thickness of the graphite nanosheets prepared by the present invention is 4.1 nm.

[0097] Example 4

[0098] Preparation of graphite nanosheets: 10g of natural flake graphite, 100g of concentrated sulfuric acid and 5g of calcium hypochlorite were mixed, reacted at 25°C for 6h, and then filtered for deacidification and washed with water; 2g of sodium carbonate was added, filtered and washed with water, 6g of concentrated hydrochloric acid was added to remove possible residual calcium ions, and filtered until the filtrate was neutral; the filter cake obtained by filtration was dried at 100°C for 5h to obtain an expandable graphite sample;

[0099] After the expandable graphite sample was expanded at 850° C. for 60 seconds in a muffle furnace, the obtained expanded graphite was dispersed in 500 mL of deionized water and sand-milled at 6000 rpm for 9 hours using 1000 g of zirconia beads (with a diameter of 2 mm) to obtain graphite nanosheets.

[0100] Preparation of modified graphite nanosheets: 5 g of the above graphite nanosheets and 300 mL of deionized water were placed in a beaker, 15 mL of hydrogen peroxide with a mass concentration of 25% was added, the beaker was placed in an ultrasonicator for ultrasonication (25° C., 1 h), and then filtered and washed with deionized water in sequence to obtain a wet filter cake (graphite nanosheets oxidized with hydrogen peroxide);

[0101] The wet filter cake was placed in a beaker, and 80 mL of deionized water and 0.15 g of sodium dodecylbenzene sulfonate (SDBS) were added at the same time. The mixture was modified in a water bath at 60° C. for 6 h, and then filtered and washed with water to obtain SDBS-modified graphite nanosheets (the filter cake was kept wet and the solid content was tested by sampling. The wet filter cake was placed in a sample bag and sealed at low temperature for storage);

[0102] Polystyrene beads doped with modified graphite nanosheets: 0.2 g (dry basis) of the SDBS-modified highly graphite nanosheets were added to a three-necked flask, and 20 g of styrene monomer, 80 mL of deionized water, 0.5 g of dibenzoyl peroxide (BPO), 0.3 g of anhydrous sodium carbonate, 0.003 g of sodium dodecylbenzene sulfonate, 0.1 g of anhydrous sodium bisulfite and 0.14 g of hydroxyapatite were added. The three-necked flask was placed in a thermostatic water bath, the initial stirring speed was adjusted to 225 rpm, the water bath temperature was adjusted to 50° C. for 1 h, and then the temperature was raised to 90° C. at a heating rate of 1° C. / min, and the stirring speed was increased to 375 rpm for 2.5 h until all the polystyrene beads were hardened and sank, and then the stirring was stopped, and the mixture was naturally cooled to room temperature, and washed repeatedly with deionized water for three times, and dried at 60° C. for 12 h to obtain polystyrene beads (particle size of 0.8-1.2 mm) doped with modified graphite nanosheets with a doping amount of 1 wt%;

[0103] Polystyrene foam doped with modified graphite nanosheets: After soaking 10 g of the polystyrene balls doped with modified graphite nanosheets in deionized water for 10 hours, the soaked doped modified graphite nanosheets are placed in a reactor, 100 mL of deionized water is added to the reactor and the reactor is closed. CO2 gas is introduced into the reactor at room temperature. When the pressure in the reactor reaches 4.5 MPa, ventilation is stopped and the temperature is slowly increased (heating rate is 15°C / 10min) to 110°C and maintained for 6 hours. The CO2 gas in the reactor is discharged within 20 seconds, the reactor is opened, and the temperature is lowered to room temperature to obtain a polystyrene foam doped with modified graphite nanosheets with a doping amount of 1wt%.

[0104] Example 5

[0105] Refer to Example 1, except that the amount of SDBS added during the preparation of the modified graphite nanosheets is 0.25 g.

[0106] Figure 6 The cross-sectional SEM image of the prepared polystyrene spheres doped with modified graphene nanosheets with a doping amount of 1 wt%. Figure 6 It can be seen that the modified graphite nanosheets are uniformly dispersed in the polystyrene beads.

[0107] Example 6

[0108] Preparation of graphite nanosheets: 10g of natural flake graphite, 100g of concentrated sulfuric acid and 5g of calcium hypochlorite were mixed, reacted at 25°C for 6h, and then filtered for deacidification and washed with water; 2g of sodium carbonate was added, filtered and washed with water, 6g of concentrated hydrochloric acid was added to remove possible residual calcium ions, and filtered until the filtrate was neutral; the filter cake obtained by filtration was dried at 100°C for 5h to obtain an expandable graphite sample;

[0109] After the expandable graphite sample was expanded at 850° C. for 60 seconds in a muffle furnace, 10 g of the obtained expanded graphite was dispersed in 500 mL of deionized water and sand-milled at 6000 rpm for 9 hours using 1000 g of zirconia beads (2 mm in diameter) to obtain graphite nanosheets.

[0110] Preparation of modified graphite nanosheets: 5 g of the above graphite nanosheets and 300 mL of deionized water were placed in a beaker, 15 mL of hydrogen peroxide with a mass concentration of 25% was added, the beaker was placed in an ultrasonicator for ultrasonication (25° C., 1 h), and then filtered and washed with deionized water in sequence to obtain a wet filter cake (graphite nanosheets oxidized with hydrogen peroxide);

[0111] The wet filter cake was placed in a beaker, and 80 mL of deionized water and 0.25 g of sodium dodecylbenzene sulfonate (SDBS) were added at the same time. The mixture was modified in a water bath at 60° C. for 6 h, and then filtered and washed with water to obtain SDBS-modified graphite nanosheets (the filter cake was kept wet and the solid content was tested by sampling. The wet filter cake was placed in a sample bag and sealed at low temperature for storage);

[0112] Polystyrene beads doped with modified graphite nanosheets: 0.4 g (dry basis) of the SDBS-modified highly graphite nanosheets were added to a three-necked flask, and 20 g of styrene monomer, 80 mL of deionized water, 1 g of dibenzoyl peroxide (BPO), 0.45 g of anhydrous sodium carbonate, 0.012 g of sodium dodecylbenzene sulfonate, 0.2 g of anhydrous sodium bisulfite and 0.42 g of hydroxyapatite were added. The three-necked flask was placed in a thermostatic water bath, the initial stirring speed was adjusted to 225 rpm, the water bath temperature was adjusted to 50° C. for 1 h, and then the temperature was raised to 90° C. at a heating rate of 1° C. / min, and the stirring speed was increased to 375 rpm for 2.5 h until all the polystyrene beads were hardened and sank, and then the stirring was stopped, and the mixture was naturally cooled to room temperature, and washed repeatedly with deionized water for three times, and dried at 60° C. for 12 h to obtain polystyrene beads (particle size of 0.8-1.2 mm) doped with modified graphite nanosheets with a doping amount of 2 wt%;

[0113] Polystyrene foam doped with modified graphite nanosheets: After soaking 10 g of the polystyrene balls doped with modified graphite nanosheets in deionized water for 10 hours, the soaked doped modified graphite nanosheets are placed in a reactor, 100 mL of deionized water is added to the reactor and the reactor is closed. CO2 gas is introduced into the reactor at room temperature. When the pressure in the reactor reaches 4.5 MPa, ventilation is stopped and the temperature is slowly increased (heating rate is 15°C / 10min) to 110°C and maintained for 6 hours. The CO2 gas in the reactor is discharged within 20 seconds, the reactor is opened, and the temperature is lowered to room temperature to obtain a polystyrene foam doped with modified graphite nanosheets with a doping amount of 2 wt%.

[0114] Example 7

[0115] Reference Example 6, the difference is that in the process of preparing polystyrene beads doped with modified graphite nanosheets, the amount of SDBS-modified highly graphite nanosheets is adjusted to 0.8 g (dry basis), the amount of dibenzoyl peroxide is 2.0 g, the amount of anhydrous sodium carbonate is 0.60 g, the amount of sodium dodecylbenzene sulfonate is 0.021 g, the amount of anhydrous sodium bisulfite is 0.3 g and the amount of hydroxyapatite is 0.70 g, and a polystyrene foam doped with modified graphite nanosheets having a doping amount of 4 wt% is obtained.

[0116] Example 8

[0117] Reference Example 6, the difference is that in the process of preparing polystyrene beads doped with modified graphite nanosheets, the amount of SDBS-modified graphite nanosheets is adjusted to 1.6 g (dry basis), the amount of dibenzoyl peroxide is 4.0 g, the amount of anhydrous sodium carbonate is 0.90 g, the amount of sodium dodecylbenzene sulfonate is 0.039 g, the amount of anhydrous sodium bisulfite is 0.5 g and the amount of hydroxyapatite is 1.29 g, and a polystyrene foam doped with modified graphite nanosheets having a doping amount of 8 wt% is obtained.

[0118] Figure 7 The cross-sectional SEM image of the prepared polystyrene spheres doped with modified graphene nanosheets with a doping amount of 8 wt%. Figure 7 It can be seen that the modified graphite nanosheets are uniformly dispersed in the polystyrene beads.

[0119] Comparative Example

[0120] Preparation of graphite nanosheets: 10g of natural flake graphite, 100g of concentrated sulfuric acid and 5g of calcium hypochlorite were mixed, reacted at 25°C for 6h, and then filtered for deacidification and washed with water; 2g of sodium carbonate was added, filtered and washed with water, 6g of concentrated hydrochloric acid was added to remove possible residual calcium ions, and filtered until the filtrate was neutral; the filter cake obtained by filtration was dried at 100°C for 5h to obtain an expandable graphite sample;

[0121] After the expandable graphite sample was expanded at 850° C. for 60 seconds in a muffle furnace, 10 g of the obtained expanded graphite was dispersed in 500 mL of deionized water and sand-milled at 6000 rpm for 9 hours using 1000 g of zirconia beads (2 mm in diameter) to obtain graphite nanosheets.

[0122] Polystyrene beads doped with graphite nanosheets: 0.2g of the graphite nanosheets (dry basis) was added to a three-necked flask, and 20g of styrene monomer, 80mL of deionized water, 0.5g of dibenzoyl peroxide (BPO), 0.3g of anhydrous sodium carbonate, 0.003g of sodium dodecylbenzene sulfonate, 0.1g of anhydrous sodium bisulfite and 0.14g of hydroxyapatite were added. The three-necked flask was placed in a constant temperature water bath, the initial stirring speed was adjusted to 225rpm, the water bath temperature was adjusted to 50°C for 1h, and then the temperature was raised to 90°C at a heating rate of 1°C / min, and the stirring speed was increased to 375rpm for 2.5h until the polystyrene beads were all hardened and sank, and then the stirring was stopped, and the mixture was naturally cooled to room temperature. After repeated washing with deionized water three times, the mixture was dried at 60°C for 12h to obtain polystyrene beads doped with graphite nanosheets with a doping amount of 1wt% (particle size of 0.8-1.2mm);

[0123] Polystyrene foam doped with modified graphite nanosheets: After soaking 10 g of the polystyrene balls doped with graphite nanosheets in deionized water for 10 hours, the soaked doped modified graphite nanosheets are placed in a reactor, 100 mL of deionized water is added to the reactor and the reactor is closed. CO2 gas is introduced into the reactor at room temperature. When the pressure in the reactor reaches 4.5 MPa, ventilation is stopped and the temperature is slowly increased (heating rate is 15°C / 10min) to 110°C and maintained for 6 hours. The CO2 gas in the reactor is discharged within 20 seconds, the reactor is opened, and the temperature is lowered to room temperature to obtain polystyrene foam doped with graphite nanosheets with a doping amount of 1wt%.

[0124] Figure 5 The XRD patterns of the polystyrene beads doped with modified graphite nanosheets and the polystyrene beads not doped with modified graphite nanosheets described in Examples 5, 6, 7, and 8 are shown in FIG. Figure 5 It can be seen that the modified graphite nanosheets are well doped into the polystyrene spheres;

[0125] Figure 8 The cross-sectional SEM image of the polystyrene spheres doped with graphite nanosheets with a doping amount of 1 wt% prepared in the comparative example is shown in FIG. Figure 8 It can be seen that unmodified graphite nanosheets cannot be well dispersed in polystyrene beads.

[0126] Test Case

[0127] The performance test was conducted on the polystyrene foam doped with modified graphite nanosheets prepared in Examples 1 to 8 and the polystyrene foam doped with graphite nanosheets with a doping amount of 1 wt % prepared in the comparative example. The test process is as follows:

[0128] 1. Antistatic performance: The polystyrene foam doped with modified graphite nanosheets prepared in Examples 1 to 8 was cut into square sheets with a side length of 10 mm and a thickness of 0.5 mm using a blade, and then the surface resistivity of the sheet was measured using an ST2648 ultra-high resistance micro-current tester;

[0129] 2. Flame retardancy: refer to ASTM D2863 to test the limiting oxygen index: the limiting oxygen index of the polystyrene foam doped with modified graphite nanosheets is obtained by testing with an oxygen index tester;

[0130] Table 1 Surface resistance and limiting oxygen index of polystyrene foams doped with modified graphite nanosheets prepared in Examples 1 to 8 and polystyrene foams doped with graphite nanosheets with a doping amount of 1 wt% prepared in the comparative example

[0131] Example <![CDATA[Surface resistance / kΩ·□ -1 > Limiting oxygen index / % Example 1 <![CDATA[5.7×10 9 ]]> 26.5 Example 2 <![CDATA[9.1×10 8 ]]> 27.8 Example 3 <![CDATA[2.0×10 8 ]]> 28.1 Example 4 <![CDATA[7.5×10 7 ]]> 28.4 Example 5 <![CDATA[9.2×10 5 ]]> 29.2 Example 6 <![CDATA[1.2×10 5 ]]> 30.1 Example 7 <![CDATA[2.5×10 4 ]]> 32.5 Example 8 <![CDATA[6.1×10 3 ]]> 35.7 Comparative Example <![CDATA[3.4×10 10 ]]> 21.8 Pure polystyrene foam <![CDATA[3.5×10 10 ]]> 18.1

[0132] As shown in Table 1, the surface modification of graphite nanosheets using sodium dodecylbenzene sulfonate after oxidation of the graphite nanosheets with hydrogen peroxide can significantly improve the doping effect of graphite nanosheets. When the amount of graphite nanosheets modified with sodium dodecylbenzene sulfonate accounts for 5wt% of the graphite nanosheets and the doping amount of the modified graphite nanosheets reaches 1wt%, the surface resistance of the doped polystyrene foam composite material is reduced by 9.2×10 5 kΩ·□ -1 (Example 5), the doped polystyrene foam composite material meets the electrostatic dissipation performance requirements; as the doping amount of modified graphite nanosheets gradually increases, the flame retardant performance of the polystyrene composite material gradually increases. When the amount of sodium dodecylbenzene sulfonate modified graphite nanosheets accounts for 1wt% of the graphite nanosheets and the doping amount of the modified graphite nanosheets reaches 1wt%, the doped polystyrene foam limiting oxygen index is 28.1% (Example 3), which meets the performance requirements of flame retardant materials.

[0133] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An antistatic, flame retardant polystyrene composite material, characterized in that: The raw materials include 0.2-1.6 parts of graphite nanosheets modified with sodium dodecylbenzene sulfonate, 20 parts of styrene monomer, 80 parts of water, 0.5-4 parts of dibenzoyl peroxide, 0.3-0.9 parts of anhydrous sodium carbonate, 0.003-0.039 parts of sodium dodecylbenzene sulfonate, 0.1-0.5 parts of anhydrous sodium bisulfite and 0.14-1.29 parts of hydroxyapatite, in parts by weight; The amount of the graphite nanosheets modified by sodium dodecylbenzene sulfonate in the antistatic and flame-retardant polystyrene composite material is 1 to 8 wt %; The method for preparing the sodium dodecylbenzenesulfonate-modified graphite nanosheets comprises the following steps: The dispersion of graphite nanosheets is mixed with hydrogen peroxide and oxidized to obtain oxidized graphite nanosheets; The oxidized graphite nanosheets, water and sodium dodecylbenzene sulfonate are mixed and modified to obtain graphite nanosheets modified with sodium dodecylbenzene sulfonate.

2. The antistatic and flame-retardant polystyrene composite material according to claim 1, characterized in that: The mass ratio of graphite nanosheets to sodium dodecylbenzene sulfonate in the dispersion of graphite nanosheets is 5:(0.05-0.25); The modification temperature is 50-85° C. and the modification time is 2-8 hours.

3. The method for preparing the antistatic and flame-retardant polystyrene composite material according to claim 1 or 2, characterized in that: The following steps are involved: The graphite nanosheets modified by sodium dodecylbenzene sulfonate, styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite are mixed and doped and polymerized to obtain polystyrene beads doped with the modified graphite nanosheets; The modified graphite nanosheet-doped polystyrene beads are soaked in water and then foamed by passing carbon dioxide to obtain the antistatic and flame-retardant polystyrene composite material.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the sodium dodecylbenzene sulfonate modified graphite nanosheets, styrene monomer, water, dibenzoyl peroxide, anhydrous sodium carbonate, sodium dodecylbenzene sulfonate, anhydrous sodium bisulfite and hydroxyapatite is (0.2-1.6):20:80:(0.5-4):(0.3-0.9):(0.003-0.039):(0.1-0.5):(0.14-1.29).

5. The preparation method according to claim 3, characterized in that: The process of the doping polymerization is as follows: at a stirring rate of 180-225 rpm, after being placed in a 40-50° C. water bath for 1-2 hours, the temperature is raised to 90-92° C. at a heating rate of 1° C. / min, the stirring speed is increased to 350-400 rpm, and the temperature is kept for 2.5-4 hours.

6. The preparation method according to claim 3, characterized in that: The foaming process is: under a pressure of 4 to 4.5 MPa, the temperature is raised to 100 to 110° C. at a heating rate of 15° C. / 10 min, and after keeping the temperature for 5 to 7 hours, carbon dioxide is discharged.

7. Use of the antistatic and flame-retardant polystyrene composite material according to claim 1 or 2 or the antistatic and flame-retardant polystyrene composite material prepared by the preparation method according to any one of claims 3 to 6 in the fields of thermal insulation and packaging of chemical equipment, electrical instruments or buildings.

Citation Information

Patent Citations

  • High flame retardancy low heat conduction graphite expandable polystyrene product and production method of same

    CN106117398A